Feminisms in Movement Theories and Practices from the Americas - De Souza Lima, Lívia; Otero Quezada, Edith; Roth, Julia (Gender Studies, 2023)
Feminist movements from the Americas provide some of the most innovative, visible, and all-encompassing forms of organizing and resistance. With their diverse backgrounds, these movements address sexism, sexualized violence, misogyny, racism, homo- and transphobia, coloniality, extractivism, climate crisis, and neoliberal capitalist exploitation as well as the interrelations of these systems. Fighting interlocking axes of oppression, feminists from the Americas represent, practice, and theorize a truly »intersectional« politics. Feminisms in Movement: Theories and Practices from the Americas brings together a wide variety of perspectives and formats, spanning from the realms of arts and activism to academia. Black and decolonial feminist voices and queer/cuir perspectives, ecofeminist approaches and indigenous women's mobilizations inspire future feminist practices and inform social and cohabitation projects. With contributions from Rita Laura Segato, Mara Viveros Vigoya, Yuderkys Espinosa-Miñoso, and interviews with Anielle Franco (Brazilian activist and minister) and with the Chilean feminist collective LASTESIS.